The Value of H2BC12 for Predicting Poor Survival Outcomes in Patients With WHO Grade II and III Gliomas - Zhou, Jie; Xing, Zhaoquan; Xiao, Yilei; Li, Mengyou; Li, Xin; Wang, Ding; Dong, Zhaogang (Frontiers in Molecular Biosciences, 2022)
Purpose: Glioma is a common primary malignant brain tumors. Gliomas grade II (GII) is prone to develop into anaplastic gliomas grade III (GIII), which indicating a higher malignancy and poorer survival outcome. This study aimed to satisfy the increasing demand of novel sensitive biomarkers and potential therapeutic targets in treatment of GII and GIII gliomas. Methods: TCGA data set was used to investigate the expression of H2BC12 mRNA in GII and GIII gliomas, and its relation with clinical pathologic characteristics. Glioams tissues were collected to verify results from TCGA data set, and H2BC12 mRNA was detected by RT-qPCR. ROC analysis was employed to evaluate the classification power for GII and GIII. The significance of H2BC12 mRNA GII and GIII gliomas was also investigated. In addition, H2BC12 expression-related pathways were enriched by gene set enrichment analysis (GSEA). DNA methylation level and mutation of H2BC12 were analyzed by UALCAN database and CBioPortal database, respectively. Results: Based on the sample data from multiple databases and RT-qPCR, higher expression of H2BC12 mRNA was found in GII and GIII gliomas tissue compared to normal tissue, which was consistent with a trend with our clinical specimen. H2BC12 mRNA had a better power in distinguishing between GII and GIII, and yielded an AUC of 0.706 with sensitivity 76.9% and specificity 81.8%. Meanwhile, high H2BC12 levels were associated with IDH status, 1p/19q codeletion, primary therapy outcome and histological type of gliomas. Moreover, overall survival (OS), disease-specific survival (DSS) and progress-free interval (PFI) of GII gliomas patients with higher level of H2BC12 were shorter than that of patients with lower level, as well as GIII patients. In the multivariate analysis, high H2BC12 level was an independent predictor for poor survival outcomes of gliomas. Pathways in cancer, Wnt or PI3K-AKT signaling pathway, DNA repair, cellular senescence and DNA double strand break repair were differentially activated in phenotype that positively associated with H2BC12. H2BC12 DNA methylation was high in TP53 nonmutant patients, and no H2BC12 mutation was observed in gliomas patients. Conclusion: H2BC12 is a promising biomarker for the diagnosis and prognosis of patients with WHO grade II and III gliomas.